Criteria for the proper interpretation of the coercive environment in the crime of sexual rape - Chero Medina, Felix (2020)
The research carried out aims to identify the criteria for applying the coercive environment that allow for the reduction of impunity in the crimes of sexual rape. It is part of a descriptive and causal study, of non-experimental design, taking as a sample collegiate judges , provincial criminal prosecutors and criminal lawyers from the city of Chiclayo; As a result of the surveys applied to justice operators, a crucial fact is that 65% do not know the specific criteria for applying the modality of the coercive environment in the crime of sexual violence, while the remaining 35% do know of the necessary application criteria for the coercive environment; which leads us to conclude that it is of utmost importance to identify through a plenary agreement the criteria to determine how the coercive environment should be applied in the crimes of sexual violation. Thus, it concluded that the evaluation criteria: a) when the victim experienced or did not consent to it under a coercive environment, b) when the coercive environment is performed by the active subject and c) when the active subject takes advantage external factors that have generated a coercive environment for the victim.